Carbon quantum dots derived from lysine and arginine simultaneously scavenge bacteria and promote tissue repair. (June 2020) - Li, Peili; Han, Fengxuan; Cao, Weiwei; Zhang, Gaoke; Li, Jiaying; Zhou, Jinwei; Gong, Xuedong; Turnbull, Gareth; Shu, Wenmiao; Xia, Lunguo; Fang, Bing; Xing, Xiaodong; et al.
Graphical abstract: Highlights: Carbon quantum dots (CQDs) were prepared by pyrolysis of lysine and arginine. CQDs effectively inhibited bacteria and promoted mammalian cell proliferation. Cationic residues and excess intracellular reactive oxygen species induced by CQDs accounted for their antibacterial effects. CQDs simultaneously scavenged bacteria and facilitated wound healing in vivo . Abstract: Effectively targeting and killing microbial pathogens is a major challenge in the treatment of infectious diseases. Inspired by the high efficacy of natural antimicrobial peptides (AMPs), in this study we prepared two types of carbon quantum dots (CQDs) by pyrolysis of lysine and arginine, the two major functional moieties of natural AMPs. Both lysine-derived CQDs (Lys-CQDs) and arginine-derived CQDs (Arg-CQDs) exhibited distinctive antibacterial activity against both Gram-negative and Gram-positive bacteria without inducing drug resistance. They also effectively inhibited the formation of bacterial biofilms. Such excellent antibacterial properties might be the result of positive charges derived from the amino acid residues on CQD surface and the generation of rich intracellular reactive oxygen species (ROS). Surprisingly, instead of being cytotoxic, CQDs dramatically promoted the growth of typical mammalian cells. Moreover, no hemolysis of red blood cells (RBCs) happened when CQD concentration was less than 4, 000 μg/mL. In vivo, administration of CQDs to infected wounds effectively inhibited bacterium growth and accelerated wound healing. Together, findings from this study indicate that Lys-CQDs and Arg-CQDs can simultaneously kill bacteria and facilitate cell growth, and may therefore be promising candidates for treating bacterial infections and promoting tissue repair.